2021
DOI: 10.1186/s13578-021-00731-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant supplements promote tumor formation and growth and confer drug resistance in hepatocellular carcinoma by reducing intracellular ROS and induction of TMBIM1

Abstract: Background Controversy over the benefits of antioxidants supplements in cancers persists for long. Using hepatocellular carcinoma (HCC) as a model, we investigated the effects of exogenous antioxidants N-acetylcysteine (NAC) and glutathione (GSH) on tumor formation and growth. Methods Multiple mouse models, including diethylnitrosamine (DEN)-induced and Trp53KO/C-MycOE-induced HCC models, mouse hepatoma cell and human HCC cell xenograft models with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Recent research reported that sorafenib can inhibit the expression of genes such as GCLC, SLC7A11 and reduce the level of glutathione (GSH), leading to the occurrence of cellular ferroptosis (Cui et al, 2022;Zhang et al, 2021). Besides nuclear events mediated by NFE2L2 and glutathione conjugation pathway, sensitive cells are active at respiratory electron transport and mitochondrial translation pathway, this means that they have more active mitochondrial reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research reported that sorafenib can inhibit the expression of genes such as GCLC, SLC7A11 and reduce the level of glutathione (GSH), leading to the occurrence of cellular ferroptosis (Cui et al, 2022;Zhang et al, 2021). Besides nuclear events mediated by NFE2L2 and glutathione conjugation pathway, sensitive cells are active at respiratory electron transport and mitochondrial translation pathway, this means that they have more active mitochondrial reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolically controlled accumulation of ROS, typical for cancer cells, induces oxidative stress and may lead to such pro-tumorigenic processes as phospholipid oxidation, DNA instability, and production of disadvantageous metal cations at a higher oxidation state. Furthermore, recent evidence has accumulated that ROS also have a role as signaling molecules in regulation cancer-cell proliferation, metastasis, angiogenesis, etc., [ 63 , 64 ] or inducing cancer-cell apoptosis [ 3 , 4 , 5 , 53 , 54 , 65 ]. It can be speculated that introduction of exogenous chemotherapeutics with antioxidant activity would affect GBM cells in a positive or negative way.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were administered R001 (5 mg/kg, oral gavage, 100 μL PBS with 5% DMSO) every day, 5 times per week for 75 days. For the R001 combination with NAC treatment, NAC was orally given alone (120 mg/kg) [ 28 ], or combined with R001 (5 mg/kg) every day, 5 times per week for 60 days. Animals were monitored daily, tumor size was measured with calipers and body weight was taken every 3–4 days.…”
Section: Methodsmentioning
confidence: 99%